Editor's Notes - Verbuč, David (Lidé města, 2022)
This year, we modestly celebrate 15 years of English editions of the Urban People / Lidé města journal. The content of this issue is more than appropriate to mark this event, as it represents our past experiences and our current achievements built on them, as well as our vision of the journal’s future. In this way, the new issue offers a culmination of our efforts and ideas toward creating a truly multimodal, inclusive, and border-defying urban anthropology journal that spans a multiplicity of countries, topics, disciplines, methodological approaches, and genres of academic exploration (i.e., academic articles, creative ethnographies, a photo essay, fieldnotes, and a book review).